Interpreting survival data from clinical trials of surgery versus stereotactic body radiation therapy in operable Stage I non-small cell lung cancer patients. (January 2017) - Samson, Pamela; Keogan, Kathleen; Crabtree, Traves; Colditz, Graham; Broderick, Stephen; Puri, Varun; Meyers, Bryan
Highlights: Trials that close with poor accrual in Stage I NSCLC have variable survival rates. Simulating trial accrual goals have survival results similar to clinical experience. Conclusions for SBRT in operable Stage I NSCLC cannot be made from such trials. Abstract: Objectives: To identify the variability of short- and long-term survival outcomes among closed Phase III randomized controlled trials with small sample sizes comparing SBRT (stereotactic body radiation therapy) and surgical resection in operable clinical Stage I non-small cell lung cancer (NSCLC) patients. Patients and methods: Clinical Stage I NSCLC patients who underwent surgery at our institution meeting the inclusion/exclusion criteria for STARS (Randomized Study to Compare CyberKnife to Surgical Resection in Stage I Non-small Cell Lung Cancer), ROSEL (Trial of Either Surgery or Stereotactic Radiotherapy for Early Stage (IA) Lung Cancer), or both were identified. Bootstrapping analysis provided 10, 000 iterations to depict 30-day mortality and three-year overall survival (OS) in cohorts of 16 patients (to simulate the STARS surgical arm), 27 patients (to simulate the pooled surgical arms of STARS and ROSEL), and 515 (to simulate the goal accrual for the surgical arm of STARS). Results: From 2000 to 2012, 749/873 (86%) of clinical Stage I NSCLC patients who underwent resection were eligible for STARS only, ROSEL only, or both studies. When patients eligible for STARS only were repeatedly sampled with a cohort size of 16, the 3-year OS rates ranged from 27 to 100%, and 30-day mortality varied from 0 to 25%. When patients eligible for ROSEL or for both STARS and ROSEL underwent bootstrapping with n = 27, the 3-year OS ranged from 46 to 100%, while 30-day mortality varied from 0 to 15%. Finally, when patients eligible for STARS were repeatedly sampled in groups of 515, 3-year OS narrowed to 70–85%, with 30-day mortality varying from 0 to 4%. Conclusion: Short- and long-term survival outcomes from trials with small sample sizes are extremely variable and unreliable for extrapolation.